DELAYED FOLLOW-UP IN PATIENTS WITH NEOVASCULAR AGE-RELATED MACULAR DEGENERATION TREATED UNDER UNIVERSAL HEALTH COVERAGE: Risk Factors and Visual Outcomes. Issue 9 (September 2022) - Rozon, Jean-Philippe; Hébert, Mélanie; Laverdière, Carolane; Lachance, Alexandre; Bourgault, Serge; Caissie, Mathieu; Letartre, Laurence; Tourville, Eric; Dirani, Ali
Abstract : Supplemental Digital Content is Available in the Text. The rate of delayed follow-up visits in patients with neovascular age-related macular degeneration treated under a universal health care system is relatively low. Delayed follow-up visits caused significant decreases in visual acuity and increases in intraretinal fluid and subretinal fluid on optical coherence tomography that did not recover after injections resumption despite normalization of central foveal thickness. Abstract : Background/Purpose: To report the rate of delayed follow-up visits (DFU), to identify risk factors of DFU, and to assess the impact of DFU on outcomes in neovascular age-related macular degeneration. Methods: This retrospective study included all patients with neovascular age-related macular degeneration (n = 1, 291) treated with antivascular endothelial growth factor injections between January 2013 and December 2020 in 2 centers in Quebec, Canada. A DFU was defined as a delay of ≥4 weeks than scheduled. Visual outcomes, especially ≥15 letters loss, were reported. Results: A total of 351 patients (27.2%) experienced ≥1 DFU. Odds were greater among older patients ( P = 0.005), patients treated at the hospital rather than the clinic ( P < 0.001), and patients with worse initial visual acuity ( P = 0.024). A DFU was associated with a mean visual acuity loss of 4.2 ± 13.4 letters ( P < 0.001) and an increased incidence of intraretinal fluid and subretinal fluid ( P = 0.001, P = 0.005) at 6 months despite resumption of injections. Central foveal thickness increased after DFU but returned to pre-DFU visit at 6 months. Conclusion: The DFU rate in patients with neovascular age-related macular degeneration treated under a universal health care system was around 27%. Delayed follow-up visits caused significant decreases in visual acuity and increases in intraretinal fluid and subretinal fluid on optical coherence tomography that did not recover after injections resumption despite normalization of central foveal thickness.